The Chemical Composition of Modern Synthetic Drugs Used to Treat Childless Disease - I. R. Asqarov; M.M.Moʻminjonov; Ashurov Sobirjon Alijon oʻgʻli (Scholars Digest Publishing, 2023)
This article provides an overview of the chemical composition of modern synthetic drugs used to treat childlessness. It examines various types of synthetic drugs used to treat infertility, their chemical composition and mechanisms of influence. The article will also discuss the possible side effects of these drugs and the importance of appropriate dosing and monitoring during treatment.
Keywords: synthetic drugs, infertility treatment, chemical composition, mechanism of influence, side effects, dosage, monitoring.